ANTIQUORUM SENSING ACTIVITY OF ESSENTIAL OILS ISOLATED FROM DIFFERENT SPECIES OF THE GENUS Piper ACTIVIDAD ANTIQUÓRUM SENSING DE ACEITES ESENCIALES AISLADOS DE DIFERENTES ESPECIES DEL GÉNERO Piper - Jesús T OLIVERO V (Universidad de Antioquia, 2011)
Quorum sensing is a bacterial communication mechanism that depends on population density, and occurs through molecules called autoinducers. These molecules activate receptors, enabling the transcription of genes that encode information needed to control several biochemical mechanisms associated with bacterial survival and pathogenicity. The aim of this study is to evaluate the inhibitory effect of essential oils of three species of Piper on the production of violacein, induced by N-hexanoyl homoserine lactone in Chromobacterium violaceum CV026. Results show that essential oils from Piper bredemeyeri, Piper brachypodom and Piper bogotence present 50% inhibitory concentration (IC50) for quorum sensing of 45.6 µg/mL, 93.1 µg/mL, and 513.8 µg/mL, respectively. However, in terms of cell growth, IC50 values for these oils are greater than 1000 µg/mL. These data suggest that essential oils isolated from Piper species found in Colombian flora are good candidates for the development of antiquorum sensing molecules, with possible applications in the control of bacterial diseases. El quórum sensing es un mecanismo de comunicación bacteriana que depende de la población celular y que ocurre a través de moléculas llamadas autoinductores, las cuales activan receptores que permiten la transcripción de genes que codifican la información necesaria para controlar diversos mecanismos bioquímicos asociados con la supervivencia y la patogenicidad bacteriana. El objetivo de este trabajo consiste en evaluar el efecto inhibitorio de los aceites esenciales de tres especies del género Piper sobre la producción de violaceína inducible por N-hexanoil homoserina lactona en Chromobacterium violaceum CV026. Los resultados señalan que los aceites esenciales de Piper bredemeyeri, Piper brachypodom y Piper bogotence poseen una concentración inhibitoria 50% (CI50) para el quórum sensing de 45.6 µg/mL, 93.1 µg/mL y 513.8 µg/mL, respectivamente. Sin embargo, en términos de crecimiento celular, el valor de CI50 para estos aceites es mayor de 1000 µg/mL. Estos datos sugieren que los aceites esenciales aislados de especies de Piper encontrados en la flora Colombiana son buenos candidatos para el desarrollo de moléculas antiquórum sensing, con posibles aplicaciones en el control de enfermedades bacterianas.